Identification and Comparative Analysis of H2O2-Scavenging Enzymes (Ascorbate Peroxidase and Glutathione Peroxidase) in Selected Plants Employing Bioinformatics Approaches - ÖZYİĞİT, İBRAHİM İLKER (FRONTIERS MEDIA SA, 2016)
Among major reactive oxygen species (ROS), hydrogen peroxide (H2O2) exhibits dual roles in plant metabolism. Low levels of H2O2 modulate many biological/physiological processes in plants; whereas, its high level can cause damage to cell structures, having severe consequences. Thus, steady-state level of cellular H2O2 must be tightly regulated. Glutathione peroxidases (GPX) and ascorbate peroxidase (APX) are two major ROS-scavenging enzymes which catalyze the reduction of H2O2 in order to prevent potential H2O2-derived cellular damage. Employing bioinformatics approaches, this study presents a comparative evaluation of both GPX and APX in 18 different plant species, and provides valuable insights into the nature and complex regulation of these enzymes. Herein, (a) potential GPX and APX genes/proteins from 18 different plant species were identified, (b) their exon/intron organization were analyzed, (c) detailed information about their physicochemical properties were provided, (d) conserved motif signatures of GPX and APX were identified, (e) their phylogenetic trees and 3D models were constructed, (f) protein-protein interaction networks were generated, and finally (g) GPX and APX gene expression profiles were analyzed. Study outcomes enlightened GPX and APX as major H2O2-scavenging enzymes at their structural and functional levels, which could be used in future studies in the current direction.
Keywords: ROS; signal transduction; antioxidant; peroxisome; chloroplast; mitochondria; OXYGEN GENE NETWORK; ARABIDOPSIS-THALIANA; MOLECULAR CHARACTERIZATION; OXIDATIVE STRESS; S-TRANSFERASE; APX1 GENE; EXPRESSION; FAMILY; SEQUENCE; TOLERANCE